ENVIRONMENTAL CONDITON, FISH RESOURCES AND MANAGEMENT OF MANINJAU LAKE OF WEST SUMATERA - Sulastri Sulastri; Dede Irving Hartoto; Ivana Yuniarti (Research Center for Fisheries, 2012)
A blooming of Microcytis aeruginosa occurred in Maninjau Lake in 2000. Mass fish killed happened frequently due to deterioration of water quality in this lake. This study is aimed to observe the current environmental condition, fishery resources status and the state of development process of comanagement regime in Maninjau Lake. Water quality parameter such as temperature, conductivity, turbidity, pH and dissolved oxygen (DO) were measured in situ by using Horiba U-10 water checker. Total nitrogen, ammonia, nitrate, nitrite, total phosphorous, orthophosohate and chlorophyll-a parameter were analyzed using standard method. Phytoplankton was analyzed by Lackey Drop Microtransect. Fish samples were obtained from fishers’ catch. Fisheries data were collected by enumerator, through Focus Group Discussion (FGD), and questioner list methods. Stakeholder analysis was conducted by focus group interview and discussion. In general, water quality parameters were suitable for the life of aquatic organisms except for DO and ammonia. These parameters indicated that the water quality of lake was still undergoing degradation process. Maninjau Lake is rich of nutrient as indicated by abundance of blue green algae. Bada fish (Rasbora argyrotaenia) is an important commodity and the fisheries significantly contributes to local people’ income. Current fisheries problems indicate the urgency of the management and conservation efforts. Several stakeholder groups showed their interest in management. The increment of institutional sustainability concern was reflected by the emergence of local wisdom and the demand for participatory development and management.